Prevotella intermedia infection causing acute and complicated aortitis—A case report. (2017) - Boersma, C.; Kampschreur, L.M.; Buter, H.; Doorenbos, B.M.; Klinkert, P.; Koning, G.G.
Highlights: Prevotella intermedia is a rare causative agent for aortitis and has, to the best knowledge of the authors, not been described in the literature before. Patients with a suspected aortitis should be referred to a vascular center with experience in the medical and surgical treatment of this specific and potentially mortal disease. Acute aortitis is a challenging clinical entity, which should be managed with a multidisciplinary team. Abstract: INTRODUCTION: Aortitis is a general term that refers to all conditions involving an inflammation of the aortic wall. This case report describes the surgical approach of a patient with infectious and symptomatic aortitis caused by the rare vector Prevotella intermedia. PRESENTATION OF CASE: A 44-year old male patient was admitted with fever and general discomfort after a period of sore throat in a non-teaching hospital. After two weeks he developed acute abdominal and back pain accompanied by sweating and elevated infection parameters. Computed tomography angiography revealed atherosclerotic changes of the infrarenal aorta with a locally contained rupture of the aorta alongside peri-aortal signs of inflammation (and aortitis aspects). An urgent aortic reconstruction was performed according to Nevelsteen. The blood cultures turned out positive for Prevotella intermedia. Postoperatively the patient received antibiotics for six weeks. The patient recovered uneventful from this infection and surgical procedure. DISCUSSION: A complicated and acute aortitis is a rare but potentially life-threatening disease. The aetiology can be ordered into two main groups; inflammatory and infectious. Diagnosis is based upon symptoms, biochemical values, microbiological results and imaging modalities. Treatment depends on aetiology and should be discussed in an experienced multidisciplinary setting. Infectious aortitis should be treated with antibiotics for at least six weeks with close monitoring of the patient's clinic and biochemical values, even after surgery. CONCLUSION: Prevotella intermedia is a rare causative agent for aortitis. Acute aortitis is a challenging clinical entity which should be managed in an equipped medical center by an experienced multidisciplinary team.